An on-line harmonics elimination PWM scheme for three-phase voltage source inverters - Salam, Z.; Safie, S. I.; Yiap, L. J. (2003)

(untitled)
An on-line harmonic elimination PWM (HEPWM) scheme for three-phase voltage source inverters is proposed. It is based on curve fitting method derived from the trajectories of the exact (off-line) HEPWM angles. The main advantage of the technique is its fast and efficient realization using a microprocessor. An outline to obtain the switching angles is presented. The method is proven by experimental results